Extraordinary Strong Band‐Edge Absorption in Distorted Chalcogenide Perovskites. Issue 5 (6th May 2020) - Nishigaki, Yukinori; Nagai, Takayuki; Nishiwaki, Mitsutoshi; Aizawa, Takuma; Kozawa, Masayuki; Hanzawa, Kota; Kato, Yoshitsune; Sai, Hitoshi; Hiramatsu, Hidenori; Hosono, Hideo; Fujiwara, Hiroyuki
Abstract : Distorted Chalcogenide Perovskites In article number 1900555, Hiroyuki Fujiwara and co‐workers show experimentally that chalcogenide perovskites (BaZrS3, SrZrS3, BaHfS3, and SrHfS3 ) exhibit an extraordinary strong light absorption of >105 cm −1 . The superior optical characteristics originate from the unique band structures of the chalcogenide perovskites, making the perovskite alloys ideal materials for the top cells of tandem solar cells, with potential efficiencies exceeding 38%.